A Digital Trail of Rupture. The German Film Exile 1933-1945 in the Data of Günter Peter Straschek - Imme Klages (Journal of Cultural Analytics)
How can digital humanities methods reveal the productivity and connectedness of a group of historical individuals linked by displacement from a country? German film exile during National Socialism, 1933-1945, has always been a complex subject to research because of the scattered nature of the sources in the international distribution of archives (Asper, Horak, Hilchenbach). It remains challenging to reconstruct the worldwide dispersed separate flight routes of more than 3000 individuals who worked for the German film industry before 1933. This contribution concerns a list of film exiles collected by the exile researcher and filmmaker Günter Peter Straschek (1942-2009), whose collection of files belongs to the _German National Library, German Exile Archive 1933-1945, Frankfurt am Main_ and was inventoried according to their Normdata. To this end, a database of GND exile data containing names, birth and death dates, professions, and countries of exile was compiled and enriched with data from online resources (Wikidata and IMDb). How can a more comprehensive look at the data reveal the devastating loss for German film (2) and, on the other hand, the collaboration on the flight (3) showing exiles remaining defiant? By incorporating new data from the Straschek Estate, digital methods further enhance historical research findings.